A promoção do desenvolvimento local e as políticas públicas de redução da vulnerabilidade social : uma análise das intervenções na temática do desenvolvimento social do Estado de Minas Gerais na última década - Nascimento, Matheus Fernandes (2021)
The objective of this research is to analyze, in a comparative perspective, state’s programs that have worked to fighting poverty and reducing social vulnerabilities of Minas Gerais’ population. There were selected some programs executed by the State Secretariat for Social Development (Sedese) in the last decade, namely: ‘Programa Travessia’, ‘Estratégia Novos Encontros’ and ‘Percursos Gerais – Trajetória para autonomia’. From the analysis of these interventions, it was sought to identify convergences and challenges that could point to effective directions for stimulating local development in the most vulnerable regions of Minas Gerais. To carry out this comparative analysis, an analytical matrix was defined, composed of dimensions related to the scope of interventions, institutional capacities, and the program’s finalistic performance. In short, it is about analyzing the planning, management, and execution of these programs. This matrix guided the information’s organization and, most importantly, enabled comparisons based on targeted criteria. The results of the study indicate that these programs, despite presenting relevant products, were not effective in their actions and were not sufficient to change the reality of social vulnerability in the localities where they operated. The discontinuity of these programs, the complexity of the phenomenon and the state's fiscal restriction scenario are factors that help explain these perceptions. Even so, it was possible to identify directions for action by the state’s government, being necessary the continuous monitoring of families in vulnerable conditions and the promotion of income generation alternatives that foster the potential and protagonism of local actors. The role of the state should be to induce alternatives to stimulate local development, organized from the integrated action of public policies and the ability to legitimize local demands. In addition, there must be a balance between economic and social policies, directing development strategies also to the most vulnerable regions.